Typology and spatial distributions of rural poverty: Evidence from Trenggalek Regency, Indonesia - Ulul Hidayah; Anggelina Delviana Klau; Suci Rahmawati Prima (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
Poverty is a condition associated with the inability to meet basic needs such as food, clothing, shelter, education, and health. Although Indonesia is currently experiencing a decline in poverty trend, data show that this extreme state of lack is consent in rural areas, such as Trenggalek Regency. Approximately 99.7% of this region is rural areas, with 10.98% poor populations. Therefore, this study aims to identify rural poverty's typology and distribution pattern in Trenggalek Regency using the spatial approach, which identifies the impact of distance and neighborhood of area towards villages’ poverty. The results showed a positive spatial autocorrelation of 0.29232, which indicates the spatial relationship between the poverty in every village in Trenggalek Regency is clustered and divided into four categories. Approximately 25, 28, 5, and 9 villages were in the high-high, low-low, low-high, and low-low categories. Every cluster has similar characteristics, thereby, the villages are influenced by each other. The results further showed that villages with high poverty rates have low accessibility to various facilities and infrastructure. An important factor that makes it possible for a rural area to escape poverty even though the surrounding is experiencing it at a higher rate is activating the micro, small and medium enterprises.JEL Classification: I32, R23, R51